Ground State Structures Of Small Boron And Boron-Carbon Clusters Via Density Functional Tight Binding And Density Functional Theory - Lian, Ming Huei (2019)
The objective of this study is to search for the ground state structure (GSS) of boron clusters (B3−B20) and boron-carbon (BC) clusters, B